Field Evaluation of Chemotherapy on HLB-Affected Citrus Trees With Emphasis on Fruit Yield and Quality - Zhang, Muqing; Karuppaiya, Palaniyandi; Zheng, Desen; Sun, Xiuxiu; Bai, Jinhe; Ferrarezi, Rhuanito S.; Powell, Charles A.; Duan, Yongping (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is one of the most devastating diseases of citrus, which is associated with Candidatus Liberibacter asiaticus (Las) in the United States. To date, no effective antimicrobial compound is commercially available to control the disease. In this study, we investigated the effects of different antimicrobial chemicals with suitable surfactants on HLB-affected matured citrus trees with emphasis on the fruit yield and quality. Each treatment was applied three times in a two-week interval during the spring flush period, one time in summer and three times during the autumn flushing period. We extensively examined different parameters such as pathogenic index, disease index, tree canopy, fruit yield, quality, and nutritional status. The results showed that among the treatments, penicillin (PEN) with surfactant was most effective in suppressing Las titer in infected citrus trees, followed by Fosetyl-Al (ALI), Carvacrol (CARV), Validamycin (VA). Fruit quality analysis revealed that PEN treatment increased the soluble solids content (SSC), whereas Oxytetracycline (OXY) treatment significantly reduced titratable acidity (TA) level and increased the SSC/TA ratio compared to the control. Nutrient analysis showed increased N and Zn levels in ALI and PEN treatments, and OXY treatment increased leaf P, K, S, and Mg levels compared to untreated control. Furthermore, B, Ca, Cu, Fe, and Mn in leaves were reduced in all chemical treatments than that of the untreated control. These findings revealed that some of the chemical treatments were able to suppress Las pathogen, enhance nutritional status in leaves, and improve tree growth and fruit quality of HLB-affected trees.